1986
DOI: 10.1128/mcb.6.2.688
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of four SIR genes of Saccharomyces cerevisiae.

Abstract: Mating type in the yeast Saccharomyces cerevisiae is determined by the MAT (a or a) locus. HML and HMR, which usually contain copies of a and a mating type information, respectively, serve as donors in mating type interconversion and are under negative transcriptional control. Four trans-acting SIR (silent information regulator) loci are required for repression of transcription. A defect in any SIR gene results in expression of both HML and HMR. The four SIR genes were isolated from a genomic library by comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
206
1
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(219 citation statements)
references
References 52 publications
10
206
1
2
Order By: Relevance
“…Arguably, silencing is best understood in molecular detail in S. cerevisiae, so the recent discovery of widespread homologues of the classically defined yeast SIR2 gene fueled the prediction that silencing, like transcriptional activation, might have conserved molecular mechanisms. SIR2's silencing-related activities include repression of transcription at the silent mating-type loci, telomeres, and within the rDNA arrays (Shore et al, 1984;Ivy et al, 1986;Aparicio et al, 1991;Bryk et al, 1997;Fritze and Esposito, 1997;Smith and Boeke, 1997), suppression of rDNA recombination (Gottlieb and Esposito, 1989), and modulation of histone (de)acetylation (Braunstein et al, 1993). We previously showed that three of four yeast homologues can function in silencing (Brachmann et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, silencing is best understood in molecular detail in S. cerevisiae, so the recent discovery of widespread homologues of the classically defined yeast SIR2 gene fueled the prediction that silencing, like transcriptional activation, might have conserved molecular mechanisms. SIR2's silencing-related activities include repression of transcription at the silent mating-type loci, telomeres, and within the rDNA arrays (Shore et al, 1984;Ivy et al, 1986;Aparicio et al, 1991;Bryk et al, 1997;Fritze and Esposito, 1997;Smith and Boeke, 1997), suppression of rDNA recombination (Gottlieb and Esposito, 1989), and modulation of histone (de)acetylation (Braunstein et al, 1993). We previously showed that three of four yeast homologues can function in silencing (Brachmann et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Among the four SIR (Silent Information Regulator) genes, SIR2 is unique because it is required for silencing and suppression of recombination within the rDNA, as well as silent mating-type (HM) and telomeric silencing (Shore et al, 1984;Ivy et al, 1986;Rine and Herskowitz, 1987;Gottlieb and Esposito, 1989;Aparicio et al, 1991;Bryk et al, 1997;Fritze and Esposito, 1997;Smith and Boeke, 1997;Smith et al, 1998). A sir2⌬ mutant strain exhibits complete derepression at these loci.…”
Section: Introductionmentioning
confidence: 99%
“…For disruption of SIR3, a DNA fragment covering the SIR3 chromosome region, containing a 2.5-kb BglII-XhoI deletion within the SIR3 coding region replaced by the 2.5-kb BglII-SalI fragment containing LEU2, was used. For disruption of SIR4, a DNA fragment covering the SIR4 chromosome region, containing a 330-bp BglII-BamHI deletion inactivating SIR4 function (15) and replaced by the 3.1-kb BglII-BglII fragment containing LEU2, was used. Disruption of SIR2, SIR3, and SIR4 genes was confirmed by the nonmating phenotype of the strains constructed.…”
Section: Methodsmentioning
confidence: 99%
“…Establishment of silencing at HM loci is under cell cycle control and requires the Sir1 protein (11,12). Sir2, Sir3, and Sir4 are required for both the establishment and the maintenance of the silenced state (13). Telomeric silencing is also influenced by the cell cycle such that it is stronger during G 1 /S and weaker during G 2 /M (14).…”
mentioning
confidence: 99%